Tata Kelola Perusahaan Oleh Dewan Direksi PT Wijaya Karya (Persero), Tbk dengan Menerapkan Prinsip Good Corporate Governance - Oi Alfa Mahardeka (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2023)
Good corporate governance is needed in the corporate world, especially PT Wijaya Karya, which is the key to the progress, success and sustainability of the company in the future. The purpose of this study is to find out how the implementation of Good Corporate Governance (GCG) at PT. Wijaya Karya, problems and settlement efforts made by PT. Wijaya Karya in applying GCG principles, and the responsibility of the board of directors in applying GCG principles to PT. Wijaya Karya. The results obtained by PT. After implementing GCG, Wijaya Karya was guided by the Minister of State-Owned Enterprises Regulation No. PER-01/MBU/2011 dated 1 August 2011 concerning the Implementation of Good Corporate Governance in BUMN and its amendments to the Regulation of the Minister of State for BUMN No. PER-09/MBU/2012 dated 6 July 2012 concerning Implementation of Good Corporate Governance for PT Wijaya Karya, with 7 basic principles of transparency, accountability, good leadership, social responsibility, effective supervision, good business ethics, and stakeholder involvement interest. PT Wijaya Karya faces several problems in implementing GCG principles, but the company has shown a strong commitment to improving GCG implementation through efforts to resolve them such as increased transparency, good leadership, social responsibility, and tighter oversight. With this strong commitment, it is hoped that PT Wijaya Karya will continue to be committed to running a sustainable and responsible business towards society and the environment.